The application of Opex & Capex system in the organisation of Tenaga Nasional Berhad in Negeri Sembilan / Khairul Fitry Khairuddin - Khairuddin, Khairul Fitry (Faculty of Business and Management, 2010)
The overall of my thesis is overview about the Opex and Capex, or also known as operating expenditure and capital expenditure. Opex and capex is the system that are applied to the most of the companies nowadays as to measure the flow of funds in the company. This is to ensure the funds that have been allocated will be fully utilized. In my thesis, the readers will be exposed to the trending of Opex and Capex itself according to the different financial year. The several ideas about the definition of Opex and Capex from the expert also were obtained from this study whose among of them have the different brilliant ideas towards this study. The ideas might give the whole new perception to the readers as it can add up the general ideas about operating and capital expenditure besides make them familiar with this study. Besides, in my thesis also will reveal the problem that always occurred in the Opex and Capex itself. The several ideas on finding the resolution on Opex and Capex were also included as it make ease to the readers in order to make them understand provided with the real scenario of Opex and Capex that happen in the company. The recommendation and conclusion will be provided in the last chapter as to conclude the overall study. The recommendation also will be given towards this study as it may add up the knowledge of the readers and also give the new dimension to embark on the problem and find the solution. This study might benefit to the readers who are undergoing in finding the resolution within their company.